2009
DOI: 10.1160/th09-01-0013
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of venous thromboembolism

Reya Gohil,
George Peck,
Pankaj Sharma

Abstract: We conducted a systematic and comprehensive meta-analysis on all candidate genes to assess their genetic contribution to the aetiology of venous thromboembolism (VTE) (pulmonary embolism and deep venous thrombosis) in all ethnic groups. Electronic databases were searched until and including January 2008 for any candidate gene investigated in VTE. Odds ratios (OR) and 95% confidence intervals (CI) were determined for each gene disease association using fixed and random effect models. Our meta-analyses included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(41 citation statements)
references
References 174 publications
(97 reference statements)
2
34
1
4
Order By: Relevance
“…Identification of genetic determinants for D-dimer levels might aid risk prediction and stratification in clinical practice, and the minor alleles in F5 and FGA are associated with increased risk of venous thromboembolism [33-34]. However, based on our current understanding of D-dimer genetics, it is not practical to simply measure SNPs identified for D-dimer levels to predict new and recurrent venous thromboembolism, because all of the SNPs identified in this and the other studies explained at most 2% of total variance in D-dimer levels.…”
Section: Discussionmentioning
confidence: 99%
“…Identification of genetic determinants for D-dimer levels might aid risk prediction and stratification in clinical practice, and the minor alleles in F5 and FGA are associated with increased risk of venous thromboembolism [33-34]. However, based on our current understanding of D-dimer genetics, it is not practical to simply measure SNPs identified for D-dimer levels to predict new and recurrent venous thromboembolism, because all of the SNPs identified in this and the other studies explained at most 2% of total variance in D-dimer levels.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 53 studies of a total of 8,364 cases found an association between the 677TT genotype and higher VTE risk, especially in non-American studies [10]. Likewise, another meta-analysis involving approximately 120,000 cases and 180,000 controls found a significant 57% increased risk of VTE in C677T homozygotes compared with heterozygotes and wild-types, in a Chinese population, whereas in Caucasians no significant association was found [11]. The MTHFR A1298C polymorphism is less well characterized but also reported to lead to increased VTE risk in the Iranian population [12].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a common F2 SNP (rs3136516 - A19911G) was also reported to be associated with increased plasma prothrombin activity and thrombosis risk in Caucasians, although at a lesser degree (27, 28, 41). Large studies and meta-analysis suggested that the rs3136516 G allele is associated with a slight increase in prothrombin activity and thrombotic risk (26, 42, 43). Prior studies (13, 2628) indicated that chromosomes carrying the rs1799963 A allele almost always had the rs3136516 A allele, which was also confirmed in our study.…”
Section: Discussionmentioning
confidence: 99%